Anti‐desmoglein 1 antibody‐positive mother and antibody‐negative child with Darier's disease. Issue 2 (8th September 2022) - Kawaguchi, Ami; Matsuda, Mitsuhiro; Koga, Hiroshi; Ohata, Chika; Hamada, Takahiro; Mishima, Hiroyuki; Yoshiura, Koh‐ichiro; Jinnin, Masatoshi; Minami, Hironori; Kanazawa, Nobuo
Abstract: We report a mother and an adult son with Darier's disease. The mother, 76 years old and Japanese, had positivity for anti‐desmoglein (Dsg)1 antibodies. She had erythema with hyperkeratosis and seborrheic and interstitial blistering. A high level of anti‐Dsg1 antibodies was detected in the serum. Histopathological examination showed acantholysis and direct immunofluorescence testing revealed intercellular IgG and C3 deposition of the epidermis. Although she was diagnosed as having pemphigus foliaceus, the skin lesions slightly improved with immunosuppressive therapy. Her son, 47 years old, had similar skin lesions on the seborrheic and interstitial parts, but the anti‐Dsg1 antibodies were negative in his serum. Histopathological examination showed acantholysis and dyskeratotic cells. Although Hailey‐Hailey disease was first suspected, no mutation in the ATP2C1 was detected in either patient. Trio‐exome analysis including the father showed a heterozygous c.2027C>A transition on exon 14 of ATP2A2, causing a replacement at amino acid 676 (p.Ala676Asp) in the mother and son only. The two patients were then diagnosed as having Darier's disease. Exome analysis further showed that a novel heterozygous missense mutation of DSG1 was identified only in the affected mother. Anti‐Dsg1 antibody‐positive Darier's disease is reported here for the first time. Very rare coexistence of Darier's disease and anti‐Dsg1 antibody‐positivity might be associated with this novel heterozygous DSG1 mutation. Experimental evidence is required to validate this hypothesis.